Study of Two-Step Parallel Cutting Technology for Deep-Hole Blasting in Shaft Excavation - Renshu Yang; Changda Zheng; Liyun Yang; Jinjing Zuo; Tonglei Cheng; Chenxi Ding; Qing Li (Shock and Vibration)
In hard rock deep-hole blasting excavation, blastholes are rarely utilized due to the clamping effect of the lower rock, which affects excavation progress and restricts the development and application of deep-hole blasting technology. Cut blasting is a key to improving excavation speed. In this paper, a new cutting method designating the two-step cutting technology was presented. The blasthole was divided into upper and lower sections without changing the blasthole layout. The upper section was detonated first, creating sufficient free surface for the lower section, which was detonated secondly. This created a larger cavity and improved blasthole utilization. Results showed good blasting effects for two-step cutting technology through theoretical analysis and engineering applications. The blasthole utilization rate was 96.1% when the upper and lower specific charge ratio = 0.78. This paper provides a good reference for resolving the low blasthole utilization problem in deep-hole blasting of vertical shafts within a hard rock.